Back Cover: Controlling Two‐Step Multimode Switching of Dihydroazulene Photoswitches (Chem. Eur. J. 10/2015). Issue 10 (19th February 2015) - Petersen, Anne U.; Broman, Søren L.; Olsen, Stine T.; Hansen, Anne S.; Du, Lin; Kadziola, Anders; Hansen, Thorsten; Kjaergaard, Henrik G.; Mikkelsen, Kurt V.; Brøndsted Nielsen, Mogens
Abstract : Two dihydroazulene photoswitches separated by a meta‐phenylene bridge can be opened sequentially to metastable vinylheptafulvene isomers under the influence of light as the intermediate species experiences reduced photoactivity due to a charge‐transfer quenching mechanism. Ultimately, both dihydroazulene units are lifted to their high‐energy vinylheptafulvene isomers, where the energy is temporarily stored. For more details, see the Full Paper by M. Brøndsted Nielsen et al. onpage 3968 ff.